Inside Cover: Comprehensive and High‐Throughput Exploration of Chemical Space Using Broadband 19F NMR‐Based Screening (Angew. Chem. Int. Ed. 35/2020). Issue 35 (4th August 2020) - Lingel, Andreas; Vulpetti, Anna; Reinsperger, Tony; Proudfoot, Andrew; Denay, Regis; Frommlet, Alexandra; Henry, Christelle; Hommel, Ulrich; Gossert, Alvar D.; Luy, Burkhard; Frank, Andreas O.
Abstract : 19 F NMR‐based fragment screening is an effective approach in pharmaceutical research to explore the chemical space for specific target–ligand interactions. In their Research Article on page 14809, A. Lingel, A. O. Frank, and co‐workers report on the development of NMR pulses that cover the entire drug‐like fluorine chemical shift range in a single experiment. The new method allows for the efficient assembly of diverse fragment libraries that can be screened for high‐quality hits within a few days.